AN INTEGRATED MULTI-CRITERIA DECISION-MAKING METHODOLOGY BASED ON TYPE-2 FUZZY SETS FOR SELECTION AMONG ENERGY ALTERNATIVES IN TURKEY - Erdogan, M.; Kaya, I. (UNIV SISTAN & BALUCHESTAN, 2015)
Energy is a critical factor to obtain a sustainable development for countries and governments. Selection of the most appropriate energy alternative is a completely critical and a complex decision making problem. In this paper, an integrated multi-criteria decision,making, (MCDM) methodology based on type-2 fuzzy sets is proposed for selection among energy alternatives. Then a roadmap has been created for Turkey. To overcome uncertainties In decision making process, the fuzzy set theory (FST) is suggested. For this aim, two of the most known MCDM methodologies are reconsidered by using type-2 fuzzy sets. Fuzzy Analytic Hierarchy Process (FAHP) based on interval type-2 fuzzy sets is constructed and is used to,obtain the weights of the criteria affecting energy alternatives. To rank the energy alternatives, the other MCDM method that is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is fuzzified by interval type-2 fuzzy sets. The proposed integrated MCDM methodology based on interval type-2 fuzzy sets is applied to obtain a road map of energy policies for Turkey.
Keywords: Energy; Multi criteria decision making; Interval type-2 fuzzy sets; AHP; TOPSIS; RENEWABLE ENERGY; MODEL; PERFORMANCE; TECHNOLOGIES; SUPPORT; SYSTEMS; DESIGN; Mathematics